Etika Dan Tanggung Jawab Sosial Pada Bisnis Internasional Sebagai Peranan Untuk Meningkatkan Kesejahteraan Rakyat - Putri Ramadhani; Hendra Ibrahim (JURNAL RISET MANAJEMEN (JURMA), 2024)
Business is an activity carried out by individuals or organizations that involves the process of making, buying, selling or exchanging goods or services with the aim of generating profits. Therefore, an idea emerged to build a business. However, you cannot do this business carelessly, you have to think about good ethics so that the business can continue to progress and develop. However, this certainly also involves the environment around us, not just the company itself. So the aim of this research is to find out ethics and social responsibility in international business as a role in improving people's welfare. This research uses a qualitative approach that describes and explains the role of ethics and social responsibility in business, especially to improve people's welfare. The results of this research show that ethics and responsibility in business have the same role which aims to improve the company's image to develop the company. A business will be hampered or unable to develop without the role of consumers. This is because, the main goal of a company, apart from making a profit, is also to attract consumer interest so as to gain the trust of consumers or business partners and help develop small businesses/farmer cooperatives through the implementation of social responsibility, at least it can encourage the economic independence of farmers provided that the implementation runs smoothly. on an ongoing basis and involving the participation of the farming community.